PENERAPAN SISTEM PERTANIAN TERPADU UNTUK MENSEJAHTERAKAN PETANI DESA - Crisna Mulya Prabowo; Mohammad Syaiful Pradana (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2022)
The integrated agricultural system is one form of a sustainable agricultural system. This system is a combination of agriculture, animal husbandry, fisheries, forestry and other sciences which are still related to agriculture in a land. By combining these several fields, it is expected to be able to increase land productivity, agricultural development programs and environmental conversion as well as efforts to improve the welfare of rural farmers. In the context of utilizing livestock waste as agricultural fertilizer, and agricultural waste as animal feed. This activity will lead to mutual benefits for each other, on the one hand the livestock is able to produce fertilizer needs and agriculture provides animal feed. This is able to add additional value to business actors so as to reduce the number of losses for each other. This activity begins with socialization to the community, then field practice and mentoring.